Letter (copy) : Position at Santander - Tewson, Vincent
037-0084-001 HVT/FC/EW/132 Secretary's 13th July, 1937. Miss E. Rathbone, M.P., House of Commons, S.W.1. Dear Miss Rathbone, Position at Santander. Many thanks for your note of the 9th inst., enclosing the statement in regard to the position at Santander. I understand that the position is now a little easier so far as shipping is concerned, but the matter is being carefully watched. Yours sincerely, Assistant Secretary. 292/946/37/84